Généalogie et usages sociaux de quatre lieux urbains paysagers à Beyrouth - Racha El-Dirani Chebbo (Projets de Paysage)
Beirut is a city that has suffered civil war starting in 1975 and lasting for 15 years, plus an Israeli invasion in 1982. Since 1990 a fragile peace still continues and a virtual line still divides this city into two parts : The western part is predominantly Muslim, the eastern part is predominantly Christian. In this tense community, there are public fora and cohabitation, but also community exclusion public spaces. What roles can do the human relationships to public space to give an identity to the landscapes and places ? This article analyzes and compares the cultural construction of the four main landscaped public spaces of Beirut.